ANALISIS KEPUASAN PENGUNJUNG TERHADAP HARGA TIKET MASUK PANBIL NATURE RESERVE BATAM - Nathania Jovita Beatrice; Okki Kurnia; Devid Trinaldo Simatupang; Nensi Lapotulo (Journal of Innovation Research and Knowledge, 2024)
Batam also has natural tourism such as Panbil Nature Reserve, the best natural tourism park in Batam that presents an adventure experience in nature with various zones and national quality activities. Its very large location makes it the most visited natural tourist spot by local residents and tourists. Based on the results of interviews with the management of Panbil Reserve Batam, they realize the importance of providing the best service in order to maintain and improve guest satisfaction with the facilities available there. However, in reality, there are still challenges in improving services. There is a lack of interest from local people to visit the place because the price is still not affordable for them or some of them are less interested in the activities provided by Panbil Nature Reserve Batam. The methodology of this study is qualitative by conducting interviews with local and foreign visitors. It can be identified that the price factor is also one of the things that can be a benchmark for visitors. Especially for local residents who still like to consider the entrance ticket price of Panbil Nature Reserve which is quite expensive for them. And one of the factors is also different habits or lifestyles that also influence local residents and foreign tourists. Foreign visitors have a healthier lifestyle and prefer many activities. While local residents tend to have a more relaxed lifestyle, and the habit of having few activities. So that there is a lack of interest from local residents to visit Panbil Nature Reserve. However, there are also local residents who have visited the place will come again, because they already understand the concept of the selling price of Panbil Nature Reserve with the facilities and services offered